2018
DOI: 10.1038/s41598-018-21260-w
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers of Hikikomori, a severe social withdrawal syndrome

Abstract: Hikikomori, a severe form of social withdrawal syndrome, is a growing social issue in Japan and internationally. The pathophysiology of hikikomori has not yet been elucidated and an effective treatment remains to be established. Recently, we revealed that avoidant personality disorder is the most common comorbidity of hikikomori. Thus, we have postulated that avoidant personality is the personality underpinning hikikomori. First, we herein show relationships between avoidant personality traits, blood biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 63 publications
(63 reference statements)
1
48
1
1
Order By: Relevance
“…Data were collected between February 2014 and December 2016. Participants completed: (i) a semi‐structured diagnostic interview for hikikomori ; (ii) the item pool for the hikikomori scale; (iii) a self‐report survey, including sociodemographic items and measures of psychiatric symptoms and psychological constructs; and (iv) a computer‐administered test and blood sample, both used for a separate research study . The hikikomori scale item pool was re‐administered to a subsample of participants for evaluation of test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected between February 2014 and December 2016. Participants completed: (i) a semi‐structured diagnostic interview for hikikomori ; (ii) the item pool for the hikikomori scale; (iii) a self‐report survey, including sociodemographic items and measures of psychiatric symptoms and psychological constructs; and (iv) a computer‐administered test and blood sample, both used for a separate research study . The hikikomori scale item pool was re‐administered to a subsample of participants for evaluation of test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported that individuals with hikikomori have higher avoidant personality scores in both sexes, and show lower serum uric acid (UA) levels in men and lower high-density lipoprotein cholesterol (HDL-C) levels in women compared with healthy volunteers. 78 This is the first report showing possible blood biomarkers for hikikomori. In addition, we have revealed that avoidant personality traits, which are strongly linked to hikikomori, are negatively associated with HDL-C and UA in men, and positively associated with fibrin degeneration products and high-sensitivity C-reactive protein in women among non-hikikomori volunteers, mainly young-adult university students.…”
Section: Biological Understandings Of Hikikomorimentioning
confidence: 84%
“…As an initial step, we are searching for biomarkers of hikikomori using human blood by recruiting actual individuals with hikikomori . We have recently reported that individuals with hikikomori have higher avoidant personality scores in both sexes, and show lower serum uric acid (UA) levels in men and lower high‐density lipoprotein cholesterol (HDL‐C) levels in women compared with healthy volunteers . This is the first report showing possible blood biomarkers for hikikomori .…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 91%
See 2 more Smart Citations